Farmers Perceptions on the Use of Insecticides For Management of Brinjal Shoot and Fruit Borer (Bangladesh Journal of Agricultural Research, 2023)
The survey was conducted in Chattogram, Jashore and Mymensingh regions of Bangladesh to find out the farmers’ knowledge and perceptions about insecticide usages in brinjal for management of brinjal shoot and fruit borer (BSFB) during August 2014 to April 2015. All the farmers of three different study areas reported that BSFB is a major problem and needs to be controlled. On an average, 91.68% farmers used conventional chemical method as main protection technique by using only insecticide whereas only 5.54% farmers used IPM method and 2.78% used different types of cultural pest management techniques for controlling BSFB. On an average, 40.80% farmers used insecticide as single form and 59.20% farmers used it in the form of cocktail. During three and half months crop season 36.35 to 57.33 times spray can occur depending on the regions. On an average, 73.23% farmers followed the advice of pesticide dealers in selecting pesticides and their doses for spraying against BSFB. Only 7.69% farmers followed the advice of extension workers which is much less as compared to the pesticide dealers. On an average, 73.98% farmers reported that insecticide was applied without any protection measures.Bangladesh J. Agril. Res. 46(4): 457-468, December 2021